2020
DOI: 10.21203/rs.3.rs-23651/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-bias in COVID-19: a meta-analysis and review of sex differences in disease and immunity

Abstract: A striking anecdotal feature of the Coronavirus disease 2019 (COVID-19) outbreak is the difference in morbidity and mortality between the sexes. Here, we present a meta-analysis of 206, 128 reported cases to demonstrate that whilst there is no difference in the proportion of males and females with confirmed COVID-19, male patients have more than double the odds of requiring intensive treatment unit admission (OR 2.5) and higher odds of death (OR 1.60) when compared to females. We review data revealing how prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 4 publications
5
27
0
2
Order By: Relevance
“…This favorable COVID-19 course, might be partially explained by the fact that all affected individuals were relatively young, which is a good prognostic feature ( Kronbichler et al., 2020 ; Oran and Topol, 2020 ) . Of note recent papers have highlighted that asymptomatic cases are more frequently young and female ( Meng et al., 2020 ; Peckham et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This favorable COVID-19 course, might be partially explained by the fact that all affected individuals were relatively young, which is a good prognostic feature ( Kronbichler et al., 2020 ; Oran and Topol, 2020 ) . Of note recent papers have highlighted that asymptomatic cases are more frequently young and female ( Meng et al., 2020 ; Peckham et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This large gender difference has been shown both in China (Guan et al, 2020;Jin et al, 2020), the first country affected by , and recently in Italy (Riccardo et al, 2020), a country that is currently, in the middle of March 2020, the most affected by this disease. A preprint reporting a meta-analysis of 39 reports, including 206,128 patients, confirms the sex bias, with much higher mortality and more severe presentation of the disease in men in several countries affected by COVID-19 throughout the world (Peckham et al, 2020). Age is another risk factor for both morbidity and mortality in COVID-19 patients, with children seemingly mostly resistant to the effects of the SARS-CoV-2 virus (Lu et al, 2020).…”
mentioning
confidence: 83%
“…Early observational findings suggested that Coronavirus disease 2019 (COVID-19) is associated with disproportionately worse outcomes in males compared to females with subsequent studies providing statistical evidence for this clinical phenomenon and indicating that morbidity and mortality are higher in males despite no difference in the proportion of infected cases between the sexes [ 1 , 2 ]. As yet, the pathogenesis behind this sex-bias is not established, although a number of theories have been proposed.…”
Section: Introductionmentioning
confidence: 99%